Crescimento econômico e política monetária endógena: a ZIRP como consequência de um baixo crescimento - Siqueira, João Vítor Pires de (2017)
The discussion on monetary policies in the history of economic thought has shaped itself facing political and economic events throughout history. From the quantitative theory of money (QTM) and the Keynesian theory to the policies of inflation targeting and zero interest rates today. This recent interest in zero interest rate policy (ZIRP) or negative interest rate (NIRP) has attracted the attention of economists, academics and policy makers. The present work aims to evaluate and to identify if the reduction of economic growth imposes or not a technical limit for the formulation of policies of interest rates. In addition, it aims to incorporate population variables into the analysis to model possible demographic impacts on interest rates, as populations in most countries are showing lower or even negative population growth rates, shifting demographics of countries towards greater representation of the older population. The possible relationships between the variables will be tested through panel data models, where annual data of interest rates, economic growth, inflation rates and demographic growth/evolution for the period from 1960 to 2015 will be used for a set of countries which adopted zero and/or negative interest rates after the 2008 crisis. The conclusion is that the aging of the population seems to restrict the possible stimulus of monetary policy, generating lower interest rates over time.